Exploring Translation Techniques and Their Translation Quality: Student’s Translators Practices Cultural Specific Items - Widyastuti, Widyastuti; Lestari, Lies Amin; Darma, Diana Budi; Adelia, Silvy Cinthia; Dianitami, Annisa Ayu; Sari, Dian Setya Purnomo (ppjbsip, 2023)
This study aims to examine translation techniques and the translation quality of the ESL student’s translation products in translating words or phrases of cultural terms. This study was a descriptive qualitative design. The data collection techniques applied content analysis. The subjects of this research were 10 English Literature study program students who have taken the Introduction to Translation course. The instrument used in this research is the text of travel writing published in Colors, an inflight magazine, which was published by the Indonesian national airline. The results of the study depicted some shifting in cultural categories, namely from the ecological category to the concept and material culture, the habit category becomes an activity category and the activity category becomes an organization in the target language. Another one is the blurred distinction between leisure and concept in religion. Implementing translation techniques that are oriented to the source text, such as pure borrowing techniques, literal translation, and established equivalences produces a high translation quality. Applying these techniques is characterized as foreignization. In short, the student's translator should be aware of not only their linguistic competence but also their transfer competence to produce a good translated text. AbstrakPenelitian ini bertujuan untuk menguji teknik penerjemahan dan kualitas terjemahan teks terjemahan mahasiswa penutur bahasa Inggris sebagai bahasa asing di dalam menerjemahkan kata atau frasa istilah-istilah budaya. Penelitian ini adalah penelitian kualitatif deskriptif. Adapun teknik pengumpulan data menggunakan analisis dokumentasi. Subyek penelitian ini yakni sepuluh mahasiswa program studi sastra Inggris yang telah menempuh mata kuliah pengantar ilmu penerjemahan. Sumber data utama berbentuk frasa dan kata yang diambil dari teks catatan perjalanan berupa majalah Color, majalah penerbangan maskapai Garuda. Hasil penelitiannya menunjukkan adanya pergeseran kategori budaya, seperti budaya ekologi bergeser menjadi budaya konsep dan material, kebiasaan menjadi aktivitas, dan aktivitas menjadi budaya organisasi. Temuan lain adalah perbedaan yang bias antara tempat wisata dan konsep beragama. Sementara penerapan teknik penerjemahan peminjaman murni, penerjemahan literal, dan padanan lazim menghasilkan kualitas terjemahan yang baik. Metode penerjemahannya berorientasi pada teks sumber. Pilihan tersebut menunjukkan ideologi forenisasi. Kesimpulan yang dapat ditarik adalah penerjemah pembelajar hendaknya dibekali kemampuan kebahasaannya dan kemampuan kompetensi mengalihkan pesan dari teks sumber ke dalam teks sasaran.